The Protective Effect of Aspirin Eugenol Ester on Paraquat-Induced Acute Liver Injury Rats - Zhang, Zhen-Dong; Yang, Ya-Jun; Liu, Xi-Wang; Qin, Zhe; Li, Shi-Hong; Li, Jian-Yong (Frontiers in Medicine, 2020)
Aspirin eugenol ester (AEE) possesses anti-inflammatory and anti-oxidative effects. The study was conducted to evaluate the protective effect of AEE on paraquat-induced acute liver injury (ALI) in rats. AEE was against ALI by decreasing alanine transaminase and aspartate transaminase levels in blood, increasing superoxide dismutase, catalase, and glutathione peroxidase levels, and decreasing malondialdehyde levels in blood and liver. Western blotting analyses showed that Bax, cytochrome C, caspase-3, caspase-9, and apoptosis-inducing factor expression levels were obviously decreased, whereas Bcl-2 expression levels obviously increased after AEE treatment. A total of 32 metabolites were identified as biomarkers by using metabolite analysis of liver homogenate based on ultra-performance liquid chromatography-tandem mass spectrometry, which belonged to purine metabolism, phenylalanine, tyrosine and tryptophan biosynthesis, glycerophospholipid metabolism, primary bile acid biosynthesis, aminoacyl-tRNA biosynthesis, phenylalanine metabolism, histidine metabolism, pantothenate and CoA biosynthesis, ether lipid metabolism, beta-Alanine metabolism, lysine degradation, cysteine and methionine metabolism. AEE exhibited protective effects on PQ-induced ALI, and the underlying mechanism is correlated with antioxidants that regulate amino acid, phospholipid and energy metabolism metabolic pathway disorders and alleviate liver mitochondria apoptosis.